2007
DOI: 10.1177/0267659108089143
|View full text |Cite
|
Sign up to set email alerts
|

Frequent sampling allows detection of short and rapid surges of exhaled ethane during cardiac surgery

Abstract: During cardiopulmonary bypass (CPB), hypoperfusion and reperfusion may cause oxidative stress and lipid peroxidation that generates ethane. The aim of this pilot study was to assess the feasibility of frequent sampling of exhaled ethane during cardiac surgery. After approval of the Research Ethics Committee, 10 patients undergoing combined aortic valve and coronary artery bypass surgery were enrolled. Breath samples were drawn in the perioperative period and analyzed by a rapid, sensitive and validated gas-chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…EXHALED ETHYLENE IN CARDIAC SURGERY lipid peroxidation (2,19,26). Firstly, our experiments reveal previously unrecognized details and magnitude of early hydrocarbon release associated with diathermy and skin incision.…”
Section: L512mentioning
confidence: 63%
See 2 more Smart Citations
“…EXHALED ETHYLENE IN CARDIAC SURGERY lipid peroxidation (2,19,26). Firstly, our experiments reveal previously unrecognized details and magnitude of early hydrocarbon release associated with diathermy and skin incision.…”
Section: L512mentioning
confidence: 63%
“…On the basis of short-chain hydrocarbon production during decomposition of omega fatty acids, the pulmonary excretion of volatile gases ethane and pentane have been considered noninvasive exhaled breath biomarkers of total body and myocardial lipid peroxidation. The milestone study of Andreoni et al (2) and subsequent studies (14,19,26) utilized discrete breath collections and laboratory analysis and provided insights into these breath biomarkers. However, there are significant inherent limitations of such methodology and significant controversy remains regarding the triggers, timing, and relevance of ethane kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors demonstrated in a swine skin incision model that the increase of the ethane in the exhaled breath is related to the use of the electrocautery [14]. Same increase of the ethane soon after the diathermy was reported later by Stenseth et al [15].…”
Section: Main Determinants Of Lipid Peroxidation During Cardiac Surge...mentioning
confidence: 84%
“…There are two principal analytical substrates that have been used to monitor oxidative stress and these are fluid phase samples including various samples obtained from the circulation or gas phase samples from the airway compartment as breath condensate. Analysis of volatile molecules in breath, including ethylene, pentane and ethane, have also been reported at various stages during cardiac surgery [13][14][15][16].…”
Section: Biomonitoring Approachesmentioning
confidence: 99%